STRUCTURING OF LOADING POINTS AND MAIN SKID ROAD IN CONDITIONS OF EXISTING ROAD NETWORK IN FOREST COMPARTMENT - Rukomojnikov, Konstantin Pavlovich (Journal of Applied Engineering Science, 2015)
The article offers the technique of choice of rational variants of placing the main skid roads in the forest compartment. This technique allows to reduce the cost of construction of loading points, skid roads and skidding of timber. The method is characterized by complex analysis of the process of logging from multiple disparate cutting areas within boundaries of the forest compartment with existing network of forest roads. The algorithmic graph theory is used in the calculations for solving this problem. The proposed method is recommended for low-volume logging companies who rent plots in limited operational forest areas.
Keywords: Graph theory; Loading point; Cutting area; Logway; Flow sheet; Skidding; Harvesting; Algorithms; Forest compartment